Viral and Cellular Factors Involved in Phloem Transport of Plant Viruses - Hipper, Clémence; Brault, Véronique; Ziegler-Graff, Véronique; Revers, Frédéric (Frontiers in Plant Science, 2013)
Phloem transport of plant viruses is an essential step in the setting-up of a complete infection of a host plant. After an initial replication step in the first cells, viruses spread from cell-to-cell through mesophyll cells, until they reach the vasculature where they rapidly move to distant sites in order to establish the infection of the whole plant. This last step is referred to as systemic transport, or long-distance movement, and involves virus crossings through several cellular barriers: bundle sheath, vascular parenchyma and companion cells for virus loading into sieve elements. Viruses are then passively transported within the source-to-sink flow of photoassimilates and are unloaded from sieve elements into sink tissues. However, the molecular mechanisms governing virus long-distance movement are far from being understood. While most viruses seem to move systemically as virus particles, some viruses are transported in sieve elements as viral ribonucleoprotein complexes (RNP). The nature of the cellular and viral factors constituting these RNPs is still poorly known. The topic of this review will mainly focus on the host and viral factors that facilitate or restrict virus long-distance movement.